IMPACT OF WORK-LIFE BALANCE ON WOMEN EMPLOYEE COMMITMENT IN EDUCATION SECTOR - Sharon, S. Sabeena; Vijayalakshmi, Prof. B. (The journal of contemporary issues in business and government, 2023)
This research article aims to “To study the impact of work life balance attributes on employee commitment in education sector”. The paper applies data reduction using Exploratory Factor Analysis (EFA) on a sample of 480 respondents drawn from educational institutions in the Bengaluru and condenses a set of 16 work life balance statement converted into a five attributes. The present study proposes a model of the impact of work life balance attributes on employee commitment in education sector. The study found that working environment, decision making power, personal role, work support and conflict with colleagues are impacting significantly the employee commitment in education sector. Therefore, educational institutions HR managers should focus on the above factors to enrich employee commitment. The study investigated the impact of work life balance attributes on employee commitment in education sector. Multiple linear regression analysis highlights that working environment, decision making power, personal role, work support and conflict with colleagues have significant impact on employee commitment in education sector.